2017
DOI: 10.1016/j.stemcr.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of Human Retinal Development from Human Pluripotent Stem Cells Generates Transplantable Populations of Cone Photoreceptors

Abstract: SummaryTransplantation of rod photoreceptors, derived either from neonatal retinae or pluripotent stem cells (PSCs), can restore rod-mediated visual function in murine models of inherited blindness. However, humans depend more upon cone photoreceptors that are required for daylight, color, and high-acuity vision. Indeed, macular retinopathies involving loss of cones are leading causes of blindness. An essential step for developing stem cell-based therapies for maculopathies is the ability to generate transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
242
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(263 citation statements)
references
References 49 publications
13
242
1
1
Order By: Relevance
“…In their studies, the electron microscopy imaging revealed other ultrastructural features of mature photoreceptors, including an outer limiting membrane, inner segments rich in mitochondria, and basal bodies with connecting cilia displaying a photoreceptor‐specific microtubule arrangement. Additional studies have obtained premature forms of stacks of outer segment discs, similar to those observed in the developing human retina .…”
Section: D Retinal Organoids Recapitulate the 3d Histoarchitecture Amentioning
confidence: 62%
See 2 more Smart Citations
“…In their studies, the electron microscopy imaging revealed other ultrastructural features of mature photoreceptors, including an outer limiting membrane, inner segments rich in mitochondria, and basal bodies with connecting cilia displaying a photoreceptor‐specific microtubule arrangement. Additional studies have obtained premature forms of stacks of outer segment discs, similar to those observed in the developing human retina .…”
Section: D Retinal Organoids Recapitulate the 3d Histoarchitecture Amentioning
confidence: 62%
“…Zhong et al , Parfitt et al , Wahlin et al , and others recently described the examples of organoid photoreceptor outer segments. In their studies, the electron microscopy imaging revealed other ultrastructural features of mature photoreceptors, including an outer limiting membrane, inner segments rich in mitochondria, and basal bodies with connecting cilia displaying a photoreceptor‐specific microtubule arrangement.…”
Section: D Retinal Organoids Recapitulate the 3d Histoarchitecture Amentioning
confidence: 99%
See 1 more Smart Citation
“…Induced pluripotent stem cell (IPSC)-derived retinal organoids have been shown to have a wide range of applications, including the study of human retinogenesis, 1-3 disease modeling, 4,5 drug discovery, 6,7 and cell therapy. [8][9][10] Numerous protocols have been developed for the generation of retinal organoids that follow basic developmental principles of forebrain development and eye formation. Despite the ability of these protocols to give rise to laminated retinal organoids, variability in the propensity of iPSCs to give rise to various retinal cell types is often reported.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous models in 2D, these 3D structures contain photoreceptors with morphologically identifiable features; including, inner segments rich in mitochondria, rudimentary outer segments with connecting cilia, and synaptic pedicles in addition to bipolar, Müller glia, ganglion and amacrine cells, synaptic layers and an outer limiting membrane, arranged in retinal layers (reviewed in (Castro et al, 2019, Capowski et al, 2019. These advanced models have proven to have many translational research applications, including transplantation studies (Pearson et al, 2016, Gonzalez-Cordero et al, 2017, probing mechanisms of retinal development (Phillips et al, 2014), and specific retinal disease modelling and testing efficacy of potential therapies in human photoreceptor cells (Parfitt et al, 2016, Deng et al, 2018, Schwarz et al, 2017, Sharma et al, 2017, Quinn et al, 2019. To date, however, they have not been used to model and rescue photoreceptor cell death.…”
Section: Introductionmentioning
confidence: 99%